Giant Vesicles (GV) in colloidal system under the Optical Polarization Microscope (OPM) - Khalid, Khalisanni; Mohd Noh, Muhammad Azri; Khan, M. Niyaz; Ishak, Ruzaina; Penney, Esther; Chowdhury, Zaira Zaman; Hamzah, Mohammad Hafiz; Othman, Maizatulnisa (Elsevier, 2017)
This paper discusses the unprecedented microscopic findings of micellar growth in colloidal system (CS) of catalyzed piperidinolysis of ionized phenyl salicylate (PS−).The giant vesicles (GV) was observed under the optical polarization microscope (OPM) at [NaX] = 0.1 M where X = 3-isopropC6H4O−. The conditions were rationalized from pseudo-first-order rate constant, kobs of PS− of micellar phase at 31.1 × 10−3 s−1 reported in previous publication. The overall diameter of GV (57.6 μm) in CS (CTABr/NaX/H2O)-catalyzed piperidinolysis (where X = 3-isopropC6H4O) of ionized phenyl salicylate were found as giant unilamellar vesicles (GUV) and giant multilamellar vesicles (GMV). The findings were also validated by means of rheological analysis.